Applying Cultural Humility During an International Collaboration Seeking to Optimize A Peaceful Coexistence Intervention in The Kingdom of Bahrain: Lessons Learned - Naglaa Rashwan; Muhsin Michael Orsini; Samantha Kelly; Francisco Pegueros; Ali Amini; Jaffar Fares; David L. Wyrick (Journal of Public Health International, 2025)
The World Health Organization emphasizes the importance of international collaboration to save lives and improve health at national and global levels. However, significant challenges face those engaged in international collaborations such as language barriers, cultural differences, different rules and regulations, and limited resources. This paper discusses the use of cultural humility theory to support an international collaboration between stakeholders from different countries with diverse cultural backgrounds working together to optimize a novel middle and high school curriculum intended to promote peaceful coexistence in the Kingdom of Bahrain. We use the attributes of cultural humility as a framework to reflect on lessons learned while navigating cultural differences, conclude by recommending the use of this framework during international collaborations, and provide practical examples about how to operationalize the attributes of cultural humility to inform international collaborations attempting to promote global public health.
Keywords: Cultural Humility